Prevalence and associated risk factors of urinary tract infection in pregnancy at the Douala General Hospital, Cameroon: a case–control study - W. W.Ch. Dayas Francine; T. Nana-Njamen; N. Omarine; D. N. Egbe; G. E. Enow-Orock; T. O. Egbe (Акушерство, гинекология и репродукция)
Introduction. The burden of urinary tract infection (UTI) in pregnancy has been understudied in Cameroon.Aim: to determine the prevalence and risk factors of UTI in pregnancy in a tertiary hospital in Cameroon.Materials and methods. A hospital-based matched case-control study of pregnant women with evidence of UTI and those without who underwent antenatal care and gave birth at the Douala General Hospital from January 2014 to December 2018. Demographic, reproductive health/clinical data were collected using a pre-tested questionnaire and analyzed with SPSS.Results. The prevalence of UTI in pregnancy was 4.41 %. Poor antenatal care uptake (AOR = 5.64; 95 % CI = 2.21–14.33), multiple weekly sexual intercourses (AOR = 4.64; 95 % CI = 0.22–96.94), a history of UTI (AOR = 3.01; 95 % CI = 1.12–8.04) and drying the genitals from back to front (AOR = 5.50; 95 % CI = 1.95–15.44) were associated factors.Conclusion. The prevalence of UTI in pregnancy is low amid multiple associated factors. Screening for UTI in pregnancy should be made the standard of obstetric care in Cameroon.